HARAPAN MASYARAKAT PADA TANGGUNG JAWAB SOSIAL PERUSAHAAN, KUALITAS PELAYANAN YANG DIRASAKAN, DAN PENGARUH MEREK PADA RETAIL BANKING DI INDONESIA - Sri Vandayuli Riorini; Andreas Wahyu Gunawan (Media Riset Bisnis & Manajemen, 2011)
The purpose of this study is to explore how customer expectation of corporate social responsibility (CSR) can influence the perceived service quality (PSQ), trust and brand affect of perspective retail banking services in Banks of the Government in Indonesia as well as to determine the affect of perceived service quality to brand affect, through the trust as an intervening variable. The design of the study is hypothesis testing. Data collected by conducting direct research into the field, which is conducted by distributing questionnaires to be filled by the respondent (customer retail banking industry). Questionnaires distributed to 120 respondents as sample of clients from government banks under Go Public category namely Bank Mandiri, Bank Negara Indonesia (BNI) and Bank Rakyat Indonesia (BRI). Sampling is done using purposive sampling technic. This study used Structural Equation Modeling as a method of data analysis. The results fmd that the customer expectation of corporate social responsibility can influence the perceived service quality, trust and brand affect. Overall, these results are consistent with previous research. CSR plays an important role in influencing the PSQ, subsequently affecting the trust, and ultimately influence the brand affect. The present study also finds a direct influence CSR on the brand affect. Although the results of this research is clear, but further research is expected to be conducted to other banks in Indonesia by considering several factors, such as the type and nature of the retail banking industry, the perception, behavior, and demographics of retail banking customers as well as the strategic focus of the retail banking toward CSR.Keywords : Corporate social responsibility, Perceived service quality, Trust, Brand affect, Banking